Grain yield of wheat cultivars of a historical sequence in Semiarid Pampa effect of nitrogen fertilization under irrigation with high salt content water (Semiárida, 2020)
In the Semiarid Central Pampa Region, with ow nitrogen content of the soils, about 26 % of the area cultivated with wheat is fertilized with nitrogen. However, water availability limits wheat production due to tow rainfall and a very marked water deficit during winter and summer. Therefore, complementary irrigation might contribute to increase the production or this crop, but the implementation of this technology has important restrictions, due to the abundance of highly saline ground water. In order to explain the yield increases due to a higher utilization or nitrogen in wheat, in modem cultivars respect to old cultivars we studied: a) a historical sequence of wheat cultivars in the Semiarid Pampa Region with respect to vegetative growth parameters and yield and b) the yield, with response of the genotypes to nitrogen fertilization with high - salt water irrigation. The experiment was carried out in, five genotypes released between 1954 and 1989. two levels of nitrogen fertilization and two levels of water availability. Our results showed that modem cultivars had a better yield index than the old ones. The yield response to nitrogen fertilization was different and the cultivars also differed in growth and yield in response to the irrigation with saline water. The grain yield response to nitrogen fertilization, in some genotypes, may not occur when irrigation with high salt content water is applied.
Keywords: Triticum aestivum; growtfi; gerotypes; saline stress